Growth of teak regenerated by coppice and stump planting in Mae Moh Plantation, Lampang province, Thailand - Auykim, Anatta; Duangsathaporn, Khwanchai; Prasomsin, Patsi (Agriculture and Natural Resources, 2017)
The current annual increment (CAIdbh) and the mean annual increment (MAIdbh) both for the diameter at breast height (1.3 m) were investigated to compare the differences between coppice and stump-planted teak in Mae Moh Plantation. Forty-eight sample cores were collected from a 9 yr-old teak plantation using an increment borer; annual increments were analyzed using dendrochronological techniques. The results indicated that there was no significant (p > 0.05) difference in the average diameter at breast height (DBH) between the coppice and stump-planted teak, whereas the total height of stump planting was significantly greater than that of coppice teak. The CAIdbh of coppice teak was in the range 0.316-2.371 cm and continuously decreased throughout the 9 yr period. The CAIdbh of stump planting was in the range 0.162-1.982 cm and continuously increased from the beginning of growth for 5 yr followed by a decline thereafter for 4 yr. The CAIdbh of coppice showed rapid growth in the years 1-4 and was greater than for the stump-planted teak even in years 5-8 after planting; however, the growth of the stumpplanted teak in the ninth year was higher than for the coppice. The MAIdbh values of coppice and stump-planted teak were not significantly (p > 0.05) different. The results showed that CAIdbh at age 5 yr can be used as a silvicultural guide to increase the yield of teak coppice.